Polysemy in Translation: A French-English Translation Of An Excerpt of Hommes/Femmes une Impossible Égalité Professionnelle? - Donkoh, J.A.D. (University of Ghana, 2021)
The aim of this project is to conduct a detailed study of polysemy as a stumbling block in translation, using the text: HOMMES/FEMMES Une impossible égalité professionnelle? as a case study. This source text which was sourced from the website of Centre Pour la Recherche Économique et ses Applications (CEPREMAP) website has been translated into English. All difficulties encountered during this translation have been documented and analysed. However, the immense problem of ambiguity which polysemy presents to translation was the main subject of this study and key examples and instances from the source text have been used as examples on how to overcome the problem of polysemy in translation. Polysemous words are ambiguous because they have several similar meanings, and are thus difficult to translate. It was however discovered that the best way to disambiguate a polyseme is to translate it within its own context.
MA. Translation
Keywords: Translation; Polysemy; Equivalence; Context; Ambiguity